Optimization of a combined wet milling process in order to produce poly(vinyl alcohol) stabilized nanosuspension - Bartos C; Jójárt-Laczkovich O; Katona G; Budai-Szűcs M; Ambrus R; Bocsik A; Gróf I; Deli MA; Szabó-Révész P (Dove Medical Press, 2018)
Csaba Bartos,1 Orsolya Jójárt-Laczkovich,1 Gábor Katona,1 Mária Budai-Szűcs,1 Rita Ambrus,1 Alexandra Bocsik,2 Ilona Gróf,2 Mária Anna Deli,2 Piroska Szabó-Révész1 1Faculty of Pharmacy, Institute of Pharmaceutical Technology and Regulatory Affairs, University of Szeged, Szeged, Hungary; 2Institute of Biophysics, Biological Research Centre, Hungarian Academy of Sciences, Szeged, Hungary Purpose: The article reports a wet milling process, where the planetary ball mill was combined with pearl milling technology to reach nanosize range of meloxicam (Mel; 100–500 nm). The main purpose was to increase the dissolution rate and extent of a poorly water-soluble Mel as nonsteroidal anti-inflammatory drug as well as to study its permeability across cultured intestinal epithelial cell layers. Methods: Viscosity of milled dispersion and particle size distribution and zeta potential of Mel were investigated and differential scanning calorimeter and X-ray powder diffractometer were used to analyse the structure of the suspended Mel. Finally in vitro dissolution test and in vitro cell culture studies were made. Results: It was found that the ratio of predispersion and pearls 1:1 (w/w) resulted in the most effective grinding system (200-fold particle size reduction in one step) with optimized process parameters, 437 rpm and 43 min. Nanosuspension (1% Mel and 0.5% poly[vinyl alcohol]) as an intermediate product showed a stable system with 2 weeks of holding time. This optimized nanosuspension enhanced the penetration of Mel across cultured intestinal epithelial cell layers without toxic effects. Conclusion: The dissolution rate of Mel from the poly(vinyl alcohol) stabilized nanosuspension justified its applicability in the design of innovative per oral dosage form (capsule) in order to ensure/give a rapid analgesia. Keywords: nanonization, meloxicam, milled dispersion, milling efficiency, zeta potential, intermediate product